Effect of endoscopic sinus surgery on eustachian tube function in adult patients with chronic rhinosinusitis - Mahmoud Atef Abdelghaffar Youssef; Nassim Talaat Nassim; MohamedNourEddin Bashir Alkeeb; Tareq Muhammad Algarf (The Egyptian Journal of Otolaryngology)
Abstract Background Chronic rhinosinusitis (CRS) is a frequent chronic heterogeneous inflammatory disease of the upper airways and paranasal sinuses persistent for ≥ 12 weeks causing considerable healthcare expenses and reduction of patients’ quality of life due to severe tiredness and disappointment as well as diminished cognitive function. CRS is commonly associated with eustachian tube (ET) dysfunction. Aim of the study To evaluate the effect of endoscopic sinus surgery on ET function in the form of (tympanogram, Valsalva maneuver, and total ET dysfunction questionnaire score), in adult patients with CRS. Method This non-randomized clinical trial study was conducted at the Otorhinolaryngology department, the Faculty of Medicine, Cairo University, on 40 patients > 18 years old, suffering from CRS with or without sinonasal polyposis who are indicated for endoscopic sinus surgery (ESS) and were recruited from Otorhinolaryngology department’s outpatient clinic in the period from November 2022 to June 2023. All selected patients were subjected to a full history taken, a full general examination, and a local otorhinolaryngology examination. Routine preoperative laboratory investigation including complete blood count (CBC), liver and kidney function tests, and coagulation profile. An electrocardiogram (ECG) examination was done routinely for all patients above 40 years old. Radiological examination included the following: preoperative CT nose and paranasal sinus, axial and coronal soft tissue cuts, and bone windows. Assessment of ET function was done using the ET dysfunction questionnaire (ETDQ-7), Valsalva maneuver, and tympanogram. ET function was reevaluated 6 weeks post-operative in the form of an ETDQ-7, Valsalva maneuver, and tympanogram. Results The ages of selected patients ranged from 21 to 45 years old with mean ± SD = 30.98 ± 10.24 years old. 52.5% of patients were males. Our results showed a statistically significant postoperative improvement in the Valsalva maneuver and the tympanogram type of both ears compared to preoperative with a p-value < 0.001. Similar results were found regarding the assessment of ET function using ETDQ-7 items and the total score (15.35 ± 4.92 vs 26.12 ± 7.79 respectively) with p-value < 0.001. Conclusion A significant improvement in ET function in the form of tympanogram, Valsalva maneuver, and total ET dysfunction questionnaire score, following endoscopic sinus surgery in adult patients with CRS with or without sinonasal polyposis.